The Politics of Artistic Labour: Rethinking a Position of Autonomy - Brazier, David (Curtin University, 2020)
While the criticality of the artist has historically been linked to the distance they produce from normative modes of “work”, today this is a distinction that ceases to exist. Through an examination of contemporary forms of labour, this research explores how the artist has entered into proximity with capital/labour relations and considers this as the site for rethinking a position of autonomy.